Investment in resources for value creation. A portfolio approach - Salinas O., Jose (1998)
To achieve success in a competitive business environment, the decisions to allocate resources in every level of the organization must focus on value creation and maximization. Further, the approach must address, not only the individual projects, but whole portfolios of proposed alternatives. For these investment project portfolios to support value creation and maximization, they must be aligned with the corporate and business unit strategies, which respond to the changes in their business environment. These changes, inherent to competitive markets, create uncertainties making the resource investment decisions difficult. Therefore, the companies must find ways to make quality decisions in the face of these uncertainties.   The approach developed by Strategic Decisions Group (SDG) allows taking investment decisions in an effective way and meets the goal of value creation and maximization in uncertain environments. This approach offers a methodology to evaluate projects, and a process to ensure quality decisions and the organizational commitment for implementation.